2013
DOI: 10.3389/fonc.2013.00134
|View full text |Cite
|
Sign up to set email alerts
|

Cisplatin Induces Differentiation of Breast Cancer Cells

Abstract: Breast tumors are heterogeneous including cells with stem cell properties and more differentiated cells. This heterogeneity is reflected into the molecular breast cancer subtypes. Breast cancer stem cells are resistant to chemotherapy, thus recent efforts are focusing on identifying treatments that shift them toward a more differentiated phenotype, making them more susceptible to chemotherapy. We examined whether the drug cisplatin induces differentiation in breast cancer cell lines that represent different br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 49 publications
4
42
0
Order By: Relevance
“…These apoptotic findings were consistent with other findings in which apoptosis was the major mechanism of cell death that appeared in MCF-7 cells following exposure to Cisplatin [18, 28]. Interestingly, the absence of nucleus in MDA-MB-231 after treatment with PBDs was observed which might be explained by the extrusion of nucleus as a way for cancer cells to die.…”
Section: Discussionsupporting
confidence: 92%
“…These apoptotic findings were consistent with other findings in which apoptosis was the major mechanism of cell death that appeared in MCF-7 cells following exposure to Cisplatin [18, 28]. Interestingly, the absence of nucleus in MDA-MB-231 after treatment with PBDs was observed which might be explained by the extrusion of nucleus as a way for cancer cells to die.…”
Section: Discussionsupporting
confidence: 92%
“…5 while the rate of necrosis did not increase significantly. Previous work of Prabhakaran et al (2013), using triple-negative BCs, BT-549, MDA-MB-231 and MDA-MB-468, along with estrogen and progesterone receptor positive MCF-7 cells, showed that the 10-20 μM CDDP treatment reduced cell viability by 36-51% and proliferation capacity by 36-67%. The authors concluded that cisplatin reduces BC cell survival showing the potential of this drug to target specific chemotherapy-resistant cells within a tumor (Prabhakaran et al, 2013).…”
Section: A B Bmentioning
confidence: 96%
“…BC are heterogeneous (Prabhakaran et al, 2013;Joensuu and Gligorov, 2012) while several risk factors have been associated with BC: age, geographic location, socio-economic status, reproductive events, hormones, lifestyle, family history of BC, mammographic density, previous benign breast disease, ionizing radiation, bone density, height, IGF-1 and prolactin levels, chemo-preventive agents (Eckstein and Haas, 2012;Dumitrescu and Cotarla, 2005;Florea and Büsselberg, 2013). Furthermore, the genetic and epigenetic backgrounds of the patients seem to play an important role in BC pathogenesis and response to chemotherapy (Normanno et al, 2009;Colombo et al, 2011) while gene expression signatures might be predictive for the patient outcome.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Breast cancer, the leading cause of death among women in the world, representing 23% of all cancer cases, is a heterogenic disease at cellular and molecular levels 1,2 . Therefore, there is an urgent need for novel drugs with an improved efficacy against breast cancer cells with minimal toxicity on normal cells.…”
Section: Introductionmentioning
confidence: 99%